The concept of a smart city in urban management - Hajduk, Sławomira (Business, Management and Economics Engineering, 2016)
Analyzing the literature covering public management, the author noticed that the urban planning is a crucial fac-tor in urban development. Cities which have an adequate intellectual resources and proper institutions as well as developed infrastructure are called smart cities. According to the author, proper local spatial development plans should be applied in those cities. Crucial parts of the city, places of the highest investors interest such as technology parks, R&D companies, business incubators, technology transfer centers and industrial complexes should definitely be incorporated in these plans. The ISO 37120 Standard is the most practical method to measure a city’s perfor-mance. The factor which decides about special management is the level of investment pressure. If this indicator is decreasing then the area does not have to be covered by local spatial development plans.This elaboration aims to examine the role of the smart city in urban management. The research shows the relationships between coverage planning, investment pressure and green areas. The main result is the author’s classification of selected 34 Medium-Size Cities in Poland. The test procedure exploited taxonomic methods as Ward’s hierarchical analysis.